Book Review: Arun Sundararajan, The Sharing Economy: The End of Employment and the Rise of Crowd-Based Capitalism. (June 2017) - Kaushal, Leena Ajit
Arun Sundararajan, The Sharing Economy: The End of Employment and the Rise of Crowd-Based Capitalism, 2016, Cambridge, Massachusetts and London, England: The MIT Press, 1–240 pp., ₹1620. ISBN: 978-0262034579. (Hardbound)